Kodrat Perempuan dalam Al-Qur’an: Sebuah Pembacaan Konstruktrivistik - Kusmana Kusmana (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2019)
This article discusses how the Qur’an and the perceptions of some Indonesian Muslim interpreters or thinkers inform and discuss the nature of women. It’s just that information and perceptions are extracted and analyzed through descriptive-analytic methods, read constructively. This study found that the concept of female nature has Qur'anic relevance, perceptual relevance and conceptual relevance. The study also found that from a constructivist perspective, women’s natural values were fluid. That is, in understanding the phenomenon of women and efforts to empower them, it is advisable to understand the perception of the nature of women who are held by the community, because what they understand and hold about the nature of women determines the spaciousness and narrowness of the region and opportunities for women’s involvement itself. In other words, failure to understand this aspect will correlate with the results of the empowerment effort.